WILD TURKEY USE OF DAIRY FARM‐TIMBERLAND HABITATS IN SOUTHEASTERN LOUISIANA - Edward P. Lambert; Winston Paul Smith; Roy D. Teitelbaum (Wildlife Society Bulletin)
Abstract: Little is known about behavior and ecology of different age and sex groups of the eastern wild turkey (Meleagris gallopavo silvestris) in domestic pine forests. During March 1983‐May 1985, 4,321 telemetry locations were recorded in 11 of 14 available habitats. Females used a greater variety of habitats and averaged larger daily movements during all seasons than males did. Except during spring, when subadult females moved greater distances than adults, subadults and adults had similar daily movement patterns. Old pine (53.8%) and hardwoods (17.1%) received the greatest overall use; old pine was a preferred habitat of males during all seasons and was preferred by females during winter and summer. Seasonal habitat use differed among age and sex groups; and within age‐sex classes, differences in habitat use occurred among seasons. Habitat use was influenced more by sex than age; the greatest disparity occurred during spring when males concentrated their activity in old pine stands (76.3%) while females apportioned use among hardwoods (19.5%), intermediate pine (30.7%), and old pine (24.7%). These data support the conclusion that life‐history needs of male and female eastern wild turkeys can be met in different habitat types. Further, the high degree of landscape diversity created by an interspersion of different age‐class pine timberland, hardwood streamside buffers, and farmland probably facilitates habitat segregation between sexes and may reduce the potential for intersexual competition, especially during the nesting season.